Sie sind auf Seite 1von 40

Chapter 6, Solution 1.

i=C
dv
dt
( )
= 5 2e −3t − 6 + e −3 t = 10(1 - 3t)e-3t A

p = vi = 10(1-3t)e-3t ⋅ 2t e-3t = 20t(1 - 3t)e-6t W

Chapter 6, Solution 2.

1 2 1
w1 = Cv1 = (40)(120) 2
2 2
1 1
w2 = Cv12 = (40)(80) 2
2 2

∆w = w 1 − w 2 = 20(120 2 − 80 2 ) = 160 kW

Chapter 6, Solution 3.

dv 280 − 160
i=C = 40x10 −3 = 480 mA
dt 5

Chapter 6, Solution 4.

1 t
C ∫o
v= idt + v(0)

1
2∫
= 6 sin 4 tdt + 1

= 1 - 0.75 cos 4t

Chapter 6, Solution 5.

1 t
C ∫o
v= idt + v(0)
For 0 < t < 1, i = 4t,
1 t
− 6 ∫o
v= 4t dt + 0 = 100t2 kV
20x10
v(1) = 100 kV
For 1 < t < 2, i = 8 - 4t,
1 t

20x10 −6 ∫1
v= (8 − 4t )dt + v(1)
= 100 (4t - t2 - 3) + 100 kV

100t 2 kV, 0 < t <1


Thus v (t) = 
100(4t − t − 2)kV, 1 < t < 2
2

Chapter 6, Solution 6.

dv
i=C = 30x10 −6 x slope of the waveform.
dt
For example, for 0 < t < 2,

dv 10
=
dt 2x10 −3
dv 10
i= C = 30x10 −6 x = 150mA
dt 2x10 −3
Thus the current i is sketched below.

i(t) (mA)
150

4 8
t (msec)

2 6 10 12

-150

Chapter 6, Solution 7.

1 1 t
∫ ∫ 4tx10
−3
v= idt + v( t o ) = dt + 10
C 50x10 −3 o

2t 2
= + 10 = 0.04k2 + 10 V
50
Chapter 6, Solution 8.

dv
(a) i = C = −100 ACe −100t − 600 BCe −600t (1)
dt

i (0) = 2 = −100 AC − 600 BC 


→ 5 = − A − 6B (2)
v (0 + ) = v (0 − ) 
→ 50 = A + B (3)
Solving (2) and (3) leads to
A=61, B=-11

1 2 1
(b) Energy = Cv (0) = x 4 x10 −3 x 2500 = 5 J
2 2

(c ) From (1),

i = −100 x61x 4 x10 −3 e −100t − 600 x11x 4 x10 −3 e −600t = − 24.4e −100t − 26.4e −600t A

Chapter 6, Solution 9.

v(t) =
1 t
12 ∫o
( ) ( )
6 1 − e − t dt + 0 = 12 t + e − t V

v(2) = 12(2 + e-2) = 25.62 V

p = iv = 12 (t + e-t) 6 (1-e-t) = 72(t-e-2t)

p(2) = 72(2-e-4) = 142.68 W

Chapter 6, Solution 10

dv dv
i=C = 2 x10 −3
dt dt

 16t , 0 < t < 1µs



v =  16, 1 < t < 3 µs
64 - 16t, 3 < t < 4 µs

 16 x10 6 , 0 < t < 1µs
dv 
=  0, 1 < t < 3 µs
dt 
- 16x10 , 3 < t < 4 µs
6

 32 kA, 0 < t < 1µs



i (t ) =  0, 1 < t < 3 µs
- 32 kA, 3 < t < 4µs

Chapter 6, Solution 11.

1 t
C ∫o
v= idt + v(0)
For 0 < t < 1,
1 t
− 6 ∫o
v= 40 x10 −3 dt = 10t kV
4x10
v(1) = 10 kV
For 1 < t < 2,
1 t
C ∫1
v= vdt + v(1) = 10kV
For 2 < t < 3,
1 t
∫ (−40x10
−3
v= )dt + v(2)
4x10 −6 2

= -10t + 30kV
Thus
10 t ⋅ kV, 0 < t <1

v(t) = 10kV, 1< t < 2
− 10 t + 30kV, 2 < t < 3

Chapter 6, Solution 12.

dv
i=C = 3x10 −3 x 60(4π)(− sin 4π t)
dt
= - 0.7e π sin 4πt A

P = vi = 60(-0.72)π cos 4π t sin 4π t = -21.6π sin 8π t W


1
t
W= ∫ o
pdt = − ∫ 8 21.6π sin 8π t dt
o
21.6π
= cos 8π 1/ 8
o = -5.4J

Chapter 6, Solution 13.

Under dc conditions, the circuit becomes that shown below:

i1 10 Ω i2 50 Ω

+ 20 Ω +

30 Ω v1 v2
− +

60V −

i2 = 0, i1 = 60/(30+10+20) = 1A

v1 = 30i2 = 30V, v2 = 60-20i1 = 40V

Thus, v1 = 30V, v2 = 40V

Chapter 6, Solution 14.

(a) Ceq = 4C = 120 mF

1 4 4
(b) = = Ceq = 7.5 mF
C eq C 30

Chapter 6, Solution 15.

In parallel, as in Fig. (a),

v1 = v2 = 100

+
v1 −

+ + C1 +
+ C1 C2 + C2
100V − v1 v2 100V − v2
− − −
(a) (b)
1 2 1
w20 = Cv = x 20x10 −6 x100 2 = 0.1J
2 2
1
w30 = x30x10 −6 x100 2 = 0.15J
2

(b) When they are connected in series as in Fig. (b):

C2 30
v1 = V= x100 = 60, v2 = 40
C1 + C 2 50

1
w20 = x30x10 −6 x 60 2 = 36 mJ
2

1
w30 = x30x10 −6 x 40 2 = 24 mJ
2

Chapter 6, Solution 16

Cx80
C eq = 14 + = 30 
→ C = 20 µF
C + 80

Chapter 6, Solution 17.

(a) 4F in series with 12F = 4 x 12/(16) = 3F


3F in parallel with 6F and 3F = 3+6+3 = 12F
4F in series with 12F = 3F
i.e. Ceq = 3F
(b) Ceq = 5 + [6 || (4 + 2)] = 5 + (6 || 6) = 5 + 3 = 8F
(c) 3F in series with 6F = (3 x 6)/9 = 6F
1 1 1 1
= + + =1
C eq 2 6 3
Ceq = 1F
Chapter 6, Solution 18.

For the capacitors in parallel


C1eq = 15 + 5 + 40 = 60 µF

1 1 1 1 1
Hence = + + =
C eq 20 30 60 10
Ceq = 10 µF

Chapter 6, Solution 19.

We combine 10-, 20-, and 30- µ F capacitors in parallel to get 60 µ F. The 60 - µ F


capacitor in series with another 60- µ F capacitor gives 30 µ F.
30 + 50 = 80 µ F, 80 + 40 = 120 µ F
The circuit is reduced to that shown below.

12 120

12 80

120- µ F capacitor in series with 80 µ F gives (80x120)/200 = 48


48 + 12 = 60
60- µ F capacitor in series with 12 µ F gives (60x12)/72 = 10 µ F

Chapter 6, Solution 20.

3 in series with 6 = 6x3/(9) = 2


2 in parallel with 2 = 4
4 in series with 4 = (4x4)/8 = 2

The circuit is reduced to that shown below:

20

1 6 2

8
6 in parallel with 2 = 8
8 in series with 8 = 4
4 in parallel with 1 = 5
5 in series with 20 = (5x20)/25 = 4

Thus Ceq = 4 mF

Chapter 6, Solution 21.

4µF in series with 12µF = (4x12)/16 = 3µF


3µF in parallel with 3µF = 6µF
6µF in series with 6µF = 3µF
3µF in parallel with 2µF = 5µF
5µF in series with 5µF = 2.5µF

Hence Ceq = 2.5µF

Chapter 6, Solution 22.

Combining the capacitors in parallel, we obtain the equivalent circuit shown below:

a b

40 µF

60 µF 30 µF

20 µF

Combining the capacitors in series gives C1eq , where


1 1 1 1 1
1
= + + = C1eq = 10µF
C eq 60 20 30 10

Thus
Ceq = 10 + 40 = 50 µF
Chapter 6, Solution 23.

(a) 3µF is in series with 6µF 3x6/(9) = 2µF


v4µF = 1/2 x 120 = 60V
v2µF = 60V
3
v6µF = (60) = 20V
6+3
v3µF = 60 - 20 = 40V

(b) Hence w = 1/2 Cv2


w4µF = 1/2 x 4 x 10-6 x 3600 = 7.2mJ
w2µF = 1/2 x 2 x 10-6 x 3600 = 3.6mJ
w6µF = 1/2 x 6 x 10-6 x 400 = 1.2mJ
w3µF = 1/2 x 3 x 10-6 x 1600 = 2.4mJ

Chapter 6, Solution 24.

20µF is series with 80µF = 20x80/(100) = 16µF

14µF is parallel with 16µF = 30µF


(a) v30µF = 90V
v60µF = 30V
v14µF = 60V
80
v20µF = x 60 = 48V
20 + 80
v80µF = 60 - 48 = 12V

1 2
(b) Since w = Cv
2
w30µF = 1/2 x 30 x 10-6 x 8100 = 121.5mJ
w60µF = 1/2 x 60 x 10-6 x 900 = 27mJ
w14µF = 1/2 x 14 x 10-6 x 3600 = 25.2mJ
w20µF = 1/2 x 20 x 10-6 x (48)2 = 23.04mJ
w80µF = 1/2 x 80 x 10-6 x 144 = 5.76mJ

Chapter 6, Solution 25.

(a) For the capacitors in series,

v1 C 2
Q1 = Q2 C1v1 = C2v2 =
v 2 C1
C2 C + C2 C1
vs = v1 + v2 = v2 + v2 = 1 v2 v2 = vs
C1 C1 C1 + C 2

C2
Similarly, v1 = vs
C1 + C 2

(b) For capacitors in parallel

Q1 Q 2
v1 = v2 = =
C1 C 2
C C + C2
Qs = Q1 + Q2 = 1 Q 2 + Q 2 = 1 Q2
C2 C2
or
C2
Q2 =
C1 + C 2
C1
Q1 = Qs
C1 + C 2

dQ C1 C2
i= i1 = is , i2 = is
dt C1 + C 2 C1 + C 2

Chapter 6, Solution 26.

(a) Ceq = C1 + C2 + C3 = 35µF

(b) Q1 = C1v = 5 x 150µC = 0.75mC


Q2 = C2v = 10 x 150µC = 1.5mC
Q3 = C3v = 20 x 150 = 3mC

1 1
(c) w= C eq v 2 = x35x150 2 µJ = 393.8mJ
2 2
Chapter 6, Solution 27.

1 1 1 1 1 1 1 7
(a) = + + = + + =
C eq C1 C 2 C 3 5 10 20 20
20
Ceq = µF = 2.857µF
7

(b) Since the capacitors are in series,


20
Q1 = Q2 = Q3 = Q = Ceqv = x 200µV = 0.5714mV
7
1 1 20
(c) w = C eq v 2 = x x 200 2 µJ = 57.143mJ
2 2 7

Chapter 6, Solution 28.

We may treat this like a resistive circuit and apply delta-wye transformation, except that
R is replaced by 1/C.

Cb 50 µF

Ca
Cc 20 µF

 1  1   1  1   1  1 
   +    +   
1 10 40 10 30 30 40
=         
Ca 1
30
3 1 1 2
= + + =
40 10 40 10

Ca = 5µF

1 1 1
+ +
1 2
= 400 300 1200 =
C6 1 30
10
Cb = 15µF
1 1 1
+ +
1 4
= 400 300 1200 =
Cc 1 15
40
Cc = 3.75µF

Cb in parallel with 50µF = 50 + 15 = 65µF


Cc in series with 20µF = 23.75µF
65x 23.75
65µF in series with 23.75µF = = 17.39µF
88.75
17.39µF in parallel with Ca = 17.39 + 5 = 22.39µF

Hence Ceq = 22.39µF

Chapter 6, Solution 29.

(a) C in series with C = C/(2)

C/2 in parallel with C = 3C/2

3C
Cx
3C 2 = 3C
in series with C =
2 C 5
5
2

C C
3 in parallel with C = C + 3 = 1.6 C
5 5

(b)

2C
Ceq
2C

1 1 1 1
= + =
C eq 2C 2C C

Ceq = C
Chapter 6, Solution 30.

1 t
C ∫o
vo = idt + i(0)
For 0 < t < 1, i = 60t mA,
10 −3 t
3x10 −6 ∫o
vo = 60tdt + 0 = 10 t 2 kV
vo(1) = 10kV

For 1< t < 2, i = 120 - 60t mA,


10 −3 t
3x10t −6 ∫1
vo = (120 − 60t )dt + v o (1)

= [40t – 10t2 ] 1 + 10kV


= 40t – 10t2 - 20
10t 2 kV, 0 < t <1
v o (t) = 
40t − 10 t − 20kV, 1 < t < 2
2

Chapter 6, Solution 31.

20 tmA, 0 < t <1


i s ( t ) = 20mA, 1< t < 3
− 50 + 10 t , 3< t <5

Ceq = 4 + 6 = 10µF
1 t
C eq ∫o
v= idt + v(0)

For 0 < t < 1,


10 −3 t
∫ 20t dt + 0 = t
2
v= kV
10x10 −6 o

For 1 < t < 3,


10 3 t
v=
10 ∫ 20dt + v(1) = 2(t − 1) + 1kV
1

= 2 t − 1kV

For 3 < t < 5,


10 3 t
v=
10 ∫ 10(t − 5)dt + v(3)
3
= t 2 − 5 + 3t +5kV = t 2 − 5t + 11kV

 t 2 kV, 0 < t <1



v( t ) = 2t − 1kV, 1< t < 3
 t − 5t + 11kV, 3 < t < 5
2

dv dv
i 1 = C1 = 6x10 −6
dt dt
12 tmA, 0 < t <1

= 12mA, 1< t < 3
12 − 30mA, 3 < t < 5

dv dv
i1 = C 2 = 4x10 −6
dt dt
8tmA, 0 < t <1

= 8mA, 1< t < 3
8t − 20mA, 3 < t < 5

Chapter 6, Solution 32.

(a) Ceq = (12x60)/72 = 10 µ F

t
10 −3
−6 ∫
t
v1 = 30e − 2t dt + v1 (0) = − 1250e − 2t 0
+ 50 = − 1250e − 2t + 1300
12 x10 0

t
10 −3
−6 ∫
t
v2 = 30e − 2t dt + v 2 (0) = 250e − 2t 0
+ 20 = 250e − 2t − 230
60 x10 0

(b) At t=0.5s,

v1 = −1250e −1 + 1300 = 840.15, v 2 = 250e −1 − 230 = −138.03

1
w12 µF = x12 x10 −6 x(840.15) 2 = 4.235 J
2

1
w20 µF = x 20 x10 −6 x(−138.03) 2 = 0.1905 J
2
1
w40 µF = x 40 x10 −6 x(−138.03) 2 = 0.381 J
2
Chapter 6, Solution 33

Because this is a totally capacitive circuit, we can combine all the capacitors using
the property that capacitors in parallel can be combined by just adding their
values and we combine capacitors in series by adding their reciprocals.

3F + 2F = 5F

1/5 +1/5 = 2/5 or 2.5F

The voltage will divide equally across the two 5F capacitors. Therefore, we get:

VTh = 7.5 V, CTh = 2.5 F

Chapter 6, Solution 34.

i = 6e-t/2
di 1
v = L = 10 x10 −3 (6) e − t / 2
dt 2
-t/2
= -30e mV

v(3) = -300e-3/2 mV = -0.9487 mV

p = vi = -180e-t mW

p(3) = -180e-3 mW = -0.8 mW

Chapter 6, Solution 35.

di V 60 x10 −3
v=L L= = = 200 mH
dt ∆i / ∆t 0.6 /(2)
Chapter 6, Solution 36.

di 1
v=L = x10 −3 (12)(2)(− sin 2 t )V
dt 4
= - 6 sin 2t mV

p = vi = -72 sin 2t cos 2t mW

But 2 sin A cos A = sin 2A

p = -36 sin 4t mW

Chapter 6, Solution 37.

di
v=L = 12 x10 −3 x 4(100) cos100t
dt
= 4.8 cos 100t V

p = vi = 4.8 x 4 sin 100t cos 100t = 9.6 sin 200t

t 11 / 200
w= ∫ pdt = ∫
o o
9.6 sin 200 t
9.6
=− cos 200t 11
o
/ 200
J
200
= −48(cos π − 1)mJ = 96 mJ

Chapter 6, Solution 38.

= 40x10 −3 (e − 2 t − 2te − 2 t )dt


di
v=L
dt
= 40(1 − 2t )e −2 t mV, t > 0
Chapter 6, Solution 39

di 1
v=L → i = ∫ 0t idt + i(0)

dt L

1
i= t
(3t 2 + 2t + 4)dt + 1
−3 ∫ 0
200x10

t
= 5( t 3 + t 2 + 4t ) +1
0

i(t) = 5t3 + 5t2 + 20t + 1 A

Chapter 6, Solution 40

di di
v=L = 20 x10 −3
dt dt

 10t , 0 < t < 1 ms



i =  20 - 10t, 1 < t < 3 ms
- 40 + 10t, 3 < t < 4 ms

 10 x10 3 , 0 < t < 1 ms
di 
= - 10x10 3 , 1 < t < 3 ms
dt 
10x10 ,
3
3 < t < 4 ms
 200 V, 0 < t < 1 ms

v = - 200 V, 1 < t < 3 ms
 200 V, 3 < t < 4 ms

which is sketched below.

v(t) V

200

0 1 2 3 4 t(ms)

-200
Chapter 6, Solution 41.

i=
1 t

L 0
1 t
( )
vdt + i(0) =   ∫ 20 1 − 2 − 2 t dt + 0.3
2 o

 1 
= 10 t + e − 2t  to +0. 3 = 10t + 5e − 2t − 4. 7 A
 2 

At t = ls, i = 10 - 4.7 + 5e-2 = 5.977 A

1 2
w= L i = 35.72J
2

Chapter 6, Solution 42.

1 t 1 t
L ∫o 5 ∫o
i= vdt + i ( 0) = v( t )dt − 1
10 t
For 0 < t < 1, i = ∫ dt − 1 = 2t − 1 A
5 0

For 1 < t < 2, i = 0 + i(1) = 1A

1
For 2 < t < 3, i =
5 ∫ 10dt + i(2) = 2t 2t +1
= 2t - 3 A

For 3 < t < 4, i = 0 + i(3) = 3 A

1 t
5 ∫4
For 4 < t < 5, i = 10dt + i(4) = 2 t 4t +3
= 2t - 5 A

 2t − 1A, 0 < t <1


 1< t < 2
1A,
Thus, i (t ) =  2t − 3 A, 2<t<3

3 A, 3<t < 4
 2t − 5, 4<t <5
Chapter 6, Solution 43.

2
t 1 1
w = L ∫ idt = Li( t ) − Li (−∞)
−∞ 2 2
1
(
= x80 x10 −3 x 60x10 −3 − 0
2
)
= 144 µJ

Chapter 6, Solution 44.

1 t 1 t
i= ∫ vdt + i(t o ) = ∫ (4 + 10 cos 2t )dt − 1
L to 5 o

= 0.8t + sin 2t -1

Chapter 6, Solution 45.

1 t
L ∫o
i(t) = v( t ) + i(0)

For 0 < t < 1, v = 5t

1 t
i=
10x10 −3 ∫ 5t dt + 0
o

= 0.25t2 kA

For 1 < t < 2, v = -10 + 5t

1 t
i=
10x10 −3 ∫ (−10 + 5t )dt + i(1)
1
t
= ∫ (0.5t − 1)dt + 0.25kA
1
= 1 - t + 0.25t2 kA

0.25t 2 kA, 0 < t <1


i( t ) = 
1 − t + 0.25t kA, 1 < t < 2
2
Chapter 6, Solution 46.

Under dc conditions, the circuit is as shown below:

2Ω
iL
+

4Ω vC
3A −

By current division,

4
iL = (3) = 2A, vc = 0V
4+2

1 2 11 2
wL = L i L =  (2) = 1J
2 22

1 1
wc = C v c2 = (2)( v) = 0J
2 2

Chapter 6, Solution 47.

Under dc conditions, the circuit is equivalent to that shown below:

+ vC − iL

2Ω
5A

2 10 10R
iL = (5) = , v c = Ri L =
R+2 R+2 R+2
1 2 100R 2
wc = Cv c = 80x10 −6 x
2 (R + 2) 2
1 100
w L = Li12 = 2x10 −3 x
2 (R + 2) 2
If wc = wL,

100R 2 2x10 −3 x100


80x10 x −6
= 80 x 10-3R2 = 2
(Rx 2) 2 (R + 2) 2

R = 5Ω

Chapter 6, Solution 48.

Under dc conditions, the circuit is as shown below:

4Ω iL1
+
iL2
+ vC2
+
30V vC1 −

− 6Ω

30
i L1 = i L 2 = = 3A
4+6

v C1 = 6i L1 = 18V

v C 2 = 0V
Chapter 6, Solution 49.

(a) L eq = 5 + 6 (1 + 4 4) = 5 + 6 3 = 7H

(b) L eq = 12 (1 + 6 6) = 12 4 = 3H

(c) L eq = 4 (2 + 3 6) = 4 4 = 2H

Chapter 6, Solution 50.

(
L eq = 10 + 5 4 12 + 3 6 )
= 10 + 5||(3 + 2) = 10 + 2.5 = 12.5 mH

Chapter 6, Solution 51.

1 1 1 1 1
= + + = L = 10 mH
L 60 20 30 10

10x35
L eq = 10 (25 + 10) =
45

= 7.778 mH

Chapter 6, Solution 52.

3//2//6 = 1H, 4//12 = 3H


After the parallel combinations, the circuit becomes that shown below.
3H
a

1H

1H b

Lab = (3+1)//1 = (4x1)/5 = 0.8 H


Chapter 6, Solution 53.

L eq = 6 + 10 + 8 [5 (8 + 12) + 6 (8 + 4)]

= 16 + 8 (4 + 4) = 16 + 4

Leq = 20 mH

Chapter 6, Solution 54.

L eq = 4 + (9 + 3) (10 0 + 6 12)

= 4 + 12 (0 + 4) = 4 + 3

Leq = 7H

Chapter 6, Solution 55.

(a) L//L = 0.5L, L + L = 2L

2 Lx0.5 L
Leq = L + 2 L // 0.5L = L + = 1.4 L
2 L + 0.5L

(b) L//L = 0.5L, L//L + L//L = L

Leq = L//L = 0.5L

Chapter 6, Solution 56.

1 L
LLL= =
3 3
L
Hence the given circuit is equivalent to that shown below:

L/3 L/3
L
5
Lx L
 2  3 = 5L
L eq = L L + L =
 3  5 8
L+ L
3

Chapter 6, Solution 57.

di
Let v = L eq (1)
dt
di
v = v1 + v 2 = 4 + v2 (2)
dt
i = i1 + i2 i2 = i – i1 (3)
di di v
v 2 = 3 1 or 1 = 2 (4)
dt dt 3
and
di di
− v2 + 2 + 5 2 = 0
dt dt
di di
v2 = 2 + 5 2 (5)
dt dt
Incorporating (3) and (4) into (5),
di di di di v
v2 = 2 + 5 − 5 1 = 7 − 5 2
dt dt dt dt 3
 5 di
v 2 1 +  = 7
 3 dt
35 di
v2 =
8 dt

Substituting this into (2) gives

di 35 di
v=4 +
dt 8 dt

67 di
=
8 dt

Comparing this with (1),

67
L eq = = 8.375H
8
Chapter 6, Solution 58.

di di
v=L = 3 = 3 x slope of i(t).
dt dt

Thus v is sketched below:

v(t) (V)
6

t (s)

1 2 3 4 5 6 7

-6

Chapter 6, Solution 59.

di
(a) v s = (L1 + L 2 )
dt
di vs
=
dt L1 + L 2
di di
v 1 = L1 , v 2 = L 2
dt dt
L1 L2
v1 = vs , vL = vs
L1 + L 2 L1 + L 2

di1 di
(b) v i = v 2 = L1 = L2 2
dt dt
i s = i1 + i 2
di s di1 di 2 v v (L + L 2 )
= + = + =v 1
dt dt dt L1 L 2 L1 L 2
1 1 L1 L 2 di s L2
i1 =
L1 ∫ vdt = ∫
L1 L1 + L 2 dt
dt =
L1 + L 2
is
1 1 L1 L 2 di s L1
i2 =
L2 ∫ vdt =
L2 ∫L 1 + L 2 dt
dt =
L 1 + L 2
is

Chapter 6, Solution 60

15
Leq = 3 // 5 =
8
vo = Leq
di 15 d
=
dt 8 dt
(
4e − 2t = − 15e − 2t )
t t
I 1 t
io =
L0∫ vo (t )dt + io (0) = 2 + ∫ (−15)e − 2t = 2 + 1.5e − 2t
50 0
= 0.5 + 1.5e − 2t A

Chapter 6, Solution 61.

(a) is = i1 + i2
i s (0) = i1 (0) + i 2 (0)
6 = 4 + i 2 ( 0) i2(0) = 2mA
(b) Using current division:
i1 =
20
30 + 20
(
i s = 0.4 6e − 2 t = 2.4e-2t mA )
i 2 = i s − i1 = 3.6e-2t mA
30 x 20
(c) 30 20 = = 12mH
50
di
v1 = L = 10x10 −3
dt
d
dt
( )
6e − 2 t x10 −3 = -120e-2t µV
di
v 2 = L = 12x10 −3
dt
d
dt
( )
6e −2 t x10 −3 = -144e-2t µV

(d) w 10 mH =
1
2
(
x30x10 −3 36e − 4 t x10 −6 )
= 0.8e − 4 t 1 µJ
t=
2

= 24.36nJ
1
(
w 30 mH = x30 x10 −3 5.76e − 4 t x10 −6 t =1 / 2
2
)
= 11.693nJ
1
(
w 20 mH = x 20x10 −3 12.96e − 4 t x10 −6 t =1 / 2
2
)
= 17.54 nJ
Chapter 6, Solution 62.

20 x60
(a) Leq = 25 + 20 // 60 = 25 + = 40 mH
80
t
di 1 10 −3
Leq ∫ 40 x10 −3 ∫0
v = Leq 
→ i= v (t ) dt + i ( 0 ) = 12e −3t dt + i (0) = −0.1(e −3t − 1) + i (0)
dt

Using current division,


60 3 1
i1 = i = i, i 2 = i
80 4 4
3
i1 (0) = i (0) → 0.75i (0) = −0.01 
→ i (0) = −0.01333
4

1
i2 = (−0.1e −3t + 0.08667) A = - 25e -3t + 21.67 mA
4
i2 (0) = −25 + 21.67 = − 3.33 mA

3
(b) i1 = (−0.1e −3t + 0.08667) A = - 75e -3t + 65 mA
4
i2 = - 25e -3t + 21.67 mA

Chapter 6, Solution 63.

We apply superposition principle and let

vo = v1 + v 2

where v1 and v2 are due to i1 and i2 respectively.

di1 di  2, 0<t <3


v1 = L =2 1 =
dt dt − 2, 3<t <6

 4, 0<t<2
di2 di2 
v2 = L =2 =  0, 2<t<4
dt dt 
− 4, 4<t<6
v1
v2

2 4

0
3 6 t 0 2 4 6 t

-2 -4

Adding v1 and v2 gives vo, which is shown below.

vo(t) V
6

0
2 3 4 6 t (s)
-2

-6

Chapter 6, Solution 64.

(a) When the switch is in position A,


i=-6 =i(0)
When the switch is in position B,
i (∞) = 12 / 4 = 3, τ = L / R = 1/ 8

i (t ) = i (∞) + [i (0) − i (∞)]e − t / ι = 3 − 9e −8t A

(b) -12 + 4i(0) + v=0, i.e. v=12 – 4i(0) = 36 V

(c) At steady state, the inductor becomes a short circuit so that


v= 0 V
Chapter 6, Solution 65.

1 1
(a) w5 = L1i12 = x5x (4) 2 = 40 W
2 2
1
w 20 = (20)(−2) 2 = 40 W
2
(b) w = w5 + w20 = 80 W
= 5(− 200)(50e − 200 t x10 −3 )
dv
(c) i1 = L1
dt
= -50e-200tA

= 20(−200)(50e − 200 t x10 −3 )


dv
i2 = L2
dt
= -200e-200tA

i2 = L2
dv
dt
(
= 20(−200) 50e − 200 t x10 −3 )
= -200e-200t A

(d) i = i1 + i2 = -250e-200t A

Chapter 6, Solution 66.

L eq = 20 + 16 + 60 40 = 36 + 24 = 60mH
di
v=L
dt
1 t
L ∫o
i= vdt + i(0)
1 t
−3 ∫o
= 12 sin 4t dt + 0 mA
60x10
i = −50 cos 4t ot = 50(1 - cos 4t) mA
60 40 = 24mH
di d
v=L = 24x10 −3 (50)(1 − cos 4t )mV
dt dt
= 4.8 sin 4t mV
Chapter 6, Solution 67.

1
RC ∫
vo = − vi dt, RC = 50 x 103 x 0.04 x 10-6 = 2 x 10-3

− 10 3
2 ∫
vo = 10 sin 50t dt
vo = 100 cos 50t mV

Chapter 6, Solution 68.

1
vo = −
RC ∫ vi dt + v(0), RC = 50 x 103 x 100 x 10-6 = 5
1 t
vo = − ∫ 10dt + 0 = −2t
5 o
The op amp will saturate at vo = ± 12

-12 = -2t t = 6s

Chapter 6, Solution 69.

RC = 4 x 106 x 1 x 10-6 = 4

1 1
vo = −
RC ∫ v i dt = − ∫ v i dt
4
1 t
4 ∫o
For 0 < t < 1, vi = 20, v o = − 20dt = -5t mV

1 t
4 ∫1
For 1 < t < 2, vi = 10, v o = − 10dt + v(1) = −2.5( t − 1) − 5
= -2.5t - 2.5mV

1 t
4 ∫2
For 2 < t < 4, vi = - 20, v o = + 20dt + v(2) = 5( t − 2) − 7.5
= 5t - 17.5 mV

1 t
4 ∫4
For 4 < t < 5m, vi = -10, v o = 10dt + v(4) = 2.5( t − 4) + 2.5
= 2.5t - 7.5 mV

1 t
4 ∫5
For 5 < t < 6, vi = 20, v o = − 20dt + v(5) = −5( t − 5) + 5
= - 5t + 30 mV
Thus vo(t) is as shown below:

25

0
1 2 3 4 5 6 7

Chapter 6, Solution 70.

One possibility is as follows:


1
= 50
RC
1
Let R = 100 kΩ, C = = 0.2µF
50 x100 x10 3

Chapter 6, Solution 71.

By combining a summer with an integrator, we have the circuit below:


+

1 1 1
vo = −
R 1C ∫ v1dt −
R 2C ∫ v 2 dt −
R 2C ∫
v 2 dt

For the given problem, C = 2µF,

R1C = 1 R1 = 1/(C) = 1006/(2) = 500 kΩ


R2C = 1/(4) R2 = 1/(4C) = 500kΩ/(4) = 125 kΩ
R3C = 1/(10) R3 = 1/(10C) = 50 kΩ
Chapter 6, Solution 72.

The output of the first op amp is

1 1 t 100 t
v1 = −
RC ∫ v i dt = −
10x10 x 2 x10 −6
3 ∫ idt = −
o 2

= - 50t

1 1 t
vo = −
RC ∫ v i dt = −
20x10 x 0.5x10 −6
3 ∫ (−50t )dt
o

= 2500t2

At t = 1.5ms,
v o = 2500(1.5) 2 x10 −6 = 5.625 mV

Chapter 6, Solution 73.

Consider the op amp as shown below:

Let va = vb = v

0 − v v − vo
At node a, = 2v - vo = 0 (1)
R R
R

R
v
a −
+
R R +
v
vo
b
+
C −
vi −

vi − v v − vo dv
At node b, = +C
R R dt
dv
v i = 2v − v o + RC (2)
dt

Combining (1) and (2),

RC dv o
v i =v o −v o +
2 dt
or
2
RC ∫
vo = v i dt

showing that the circuit is a noninverting integrator.

Chapter 6, Solution 74.

RC = 0.01 x 20 x 10-3 sec

dv i dv
v o = − RC = −0.2 m sec
dt dt

 − 2V, 0 < t <1


v o = 2V, 1< t < 3
− 2V, 3< t < 4

Thus vo(t) is as sketched below:

vo(t) (V)
2

t (ms)

1 2 3

-2
Chapter 6, Solution 75.

dv i
v 0 = − RC , RC = 250 x10 3 x10x10 −6 = 2.5
dt

d
v o = −2.5 (12t ) = -30 mV
dt

Chapter 6, Solution 76.

dv i
v o = − RC , RC = 50 x 103 x 10 x 10-6 = 0.5
dt
dv − 10, 0 < t < 5
v o = 0.5 i = 
dt 5, 5<t <5

The input is sketched in Fig. (a), while the output is sketched in Fig. (b).

vo(t) (V)
vi(t) (V)

5 5

t (ms) t (ms)

0 5 10 15 0 5 10 15

(a)

-10

(b)

Chapter 6, Solution 77.

i = iR + i C

vi − 0 0 − v0 d
= + C (0 − v o )
R RF dt
R F C = 10 6 x10 −6 = 1
 dv 
Hence v i = − v o + o 
 dt 

Thus vi is obtained from vo as shown below:

– vo(t) (V) –dvo(t)/dt

4 4

t (ms) t (ms)

0 1 2 3 4 0 1 2 3 4

-4 -4

vi(t) (V)

t (ms)

-4 1 2 3 4

-8

Chapter 6, Solution 78.

d 2 vo 2dv o
= 10 sin 2 t − − vo
dt dt

Thus, by combining integrators with a summer, we obtain the appropriate analog


computer as shown below:
2vo
− + t=0
C
C
R
R
R
− R
d2vo/dt −
+ −
2 +
-dvo/dt + d2vo/dt
vo 2
R R

R/2

+ dvo/dt
R
R
R/10

+
+
sin2t − -sin2t

Chapter 6, Solution 79.


We can write the equation as
dy
= f (t ) − 4 y (t )
dt
which is implemented by the circuit below.

1V t=0

C R R

R
R/4 R
dy/dt - - -
+ -y + +
R dy/dt

f(t)
Chapter 6, Solution 80.

From the given circuit,

d 2 vo 1000kΩ 1000kΩ dv o
= f (t) − vo −
dt 2
5000kΩ 200kΩ dt
or
d 2 vo dv
2
+ 5 o + 2v o = f ( t )
dt dt

Chapter 6, Solution 81

We can write the equation as

d 2v
= −5v − 2 f (t )
dt 2

which is implemented by the circuit below.

C C
R

R
- R R/5
2 2
d v/dt + -
-dv/dt + v -
+ d2v/dt2
R/2
f(t)
Chapter 6, Solution 82

The circuit consists of a summer, an inverter, and an integrator. Such circuit is shown
below.

10R R

R R
-
+ - vo
+
R

C=1/(2R)

R
-
+ +
vs
-

Chapter 6, Solution 83.

Since two 10µF capacitors in series gives 5µF, rated at 600V, it requires 8 groups in
parallel with each group consisting of two capacitors in series, as shown below:

+
600

Answer: 8 groups in parallel with each group made up of 2 capacitors in series.


Chapter 6, Solution 84.

∆q
∆I = ∆I x ∆t = ∆q
∆t

∆q = 0.6 x 4 x 10-6
= 2.4µC

∆q 2.4 x10−6
C= = = 150nF
∆v (36 − 20)

Chapter 6, Solution 85.

It is evident that differentiating i will give a waveform similar to v. Hence,


di
v=L
dt

4 t ,0 < t < 1
i=
8 − 4 t ,1 < t < 2

di 4L,0 < t < 1


v=L =
dt − 4L,1 < t < 2

5mV,0 < t < 1


But, v=
− 5mV,1 < t < 2

Thus, 4L = 5 x 10-3 L = 1.25 mH in a 1.25 mH inductor

Chapter 6, Solution 86.

(a) For the series-connected capacitor

1 C
Cs = =
1 1 1 8
+ + .... +
C C C

For the parallel-connected strings,

10C s 1000
C eq = 10C s = = 10 x µF = 1250µF
8 3
(b) vT = 8 x 100V = 800V

w=
1
2
(
1
)
C eq v T2 = 1250 x10 −6 (800) 2
2

= 400J